POLITICAL EFFICACY AND POLITICAL PARTICIPATION IN ISLAMIC ASSOCIATION CADRES: POLITICAL EFFICACY AND POLITICAL PARTICIPATION IN ISLAMIC ASSOCIATION CADRES - Prahara, Sowanya Ardi; Rachma, Nur Mujahidah (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Student organizations have a role in the political process, guarding government policies with their movements and contributing their intelligence as students to achieve a renewal of the Indonesian nation. This study examines the relationship between political efficacy and political participation in student organization cadres. The research method used in this study is a quantitative method with a Likert scale. The subjects in this study amounted to 92 Islamic Student Association cadres with characteristics with a membership period of at least six months, an age range of 18 years, and the highest being 24 years. This study adjusted and adapted the Political Participation and Efficacy scales based on theory. The data analysis technique used in this study uses product-moment correlation. The study found a significant relationship between political efficacy and political participation in Islamic association cadres.